Phosphorus-carbon negative electrode material, battery as well as preparation method and application of phosphorus-carbon negative electrode material
By using the phosphorus-carbon anode material and cladding layer with a core structure in lithium-ion batteries, combined with organic nitrile additives, the volume expansion problem of phosphorus-based anode material is solved, the cycle stability and energy density of the battery are improved, and the battery is extended life.
Patent Information
- Application Number
- CN202411326123.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-01-10
AI Technical Summary
The volume expansion of the phosphorus-based negative electrode material during charging and discharging of lithium-ion batteries leads to damage to the electrode microstructure and the interface instability of the solid electrolyte, reducing the cyclic stability and life of the battery.
The negative electrode material with a putaway structure is used, and the cladding layer is composed of LiF, Li3N, Li3PO4, Li2B4O7, Li4Ti5O12, etc., to inhibit the volume expansion of the phosphorus material, and add organic nitrile additives to the electrolyte to reduce high-temperature decomposition and side reactions.
Effectively stabilize the circulation process of negative electrode materials, improve the circulation stability and energy density of lithium-ion batteries, reduce volume expansion and high-temperature gas production problems, and extend battery life.
Smart Images

Figure BDA0005055468030000241
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a phosphorus-carbon negative electrode material, a battery, and a preparation method and application thereof. Background Art
[0002] Among many negative electrode materials, phosphorus-based negative electrode has a high theoretical specific capacity and lithiation potential, and is a fast-charging, high-specific-capacity lithium-ion battery negative electrode material with great application potential. Negative electrode materials are an important component of lithium-ion batteries, and their main function is to carry and release lithium ions during the charge and discharge process. Phosphorus-based negative electrode materials have attracted extensive research attention due to their rich lithium storage sites and superior electrochemical properties.
[0003] Phosphorus-based negative electrode materials refer to materials with phosphorus as the main component, such as silicon phosphide, carbon phosphide, etc. Compared with traditional carbon-based materials, phosphorus-based negative electrode materials have higher theoretical specific capacity and can store more lithium ions, thereby improving the energy density of the battery. In addition, phosphorus-based negative electrode materials usually have lower electrode reaction potential, which is beneficial to the battery's charge and discharge efficiency and fast charging characteristics.
[0004] However, phosphorus-based anode materials also have some significant disadvantages. One of the main problems is the volume expansion that occurs during the charge and discharge process. The volume of phosphorus-based material particles changes significantly during lithium insertion (charging) and deinsertion (discharging) due to the change in the lattice structure caused by the adsorption and release of lithium ions. This volume change not only leads to the destruction of the electrode microstructure, but also causes instability of the solid electrolyte interface (SEI film) in the battery.
[0005] The SEI film plays a key role in lithium-ion batteries, stabilizing the battery's charge and discharge process and preventing direct contact between the electrode and the electrolyte. However, the instability of the SEI film caused by the volume expansion of phosphorus-based negative electrode materials can cause the interface between the electrode material and the electrolyte to become uneven, thereby increasing the battery's internal resistance and reducing the battery's cycle stability and life.
[0006] Although phosphorus-based anode materials have high theoretical energy density and fast charging characteristics, their volume expansion effect limits their performance in practical applications.
[0007] Therefore, there is an urgent need to develop a negative electrode that can suppress the volume change of phosphorus materials, and a battery loaded with the negative electrode and having high cycle stability. Summary of the invention
[0008] An object of the present invention is to provide a lithium ion battery with high cycle stability.
[0009] A first aspect of the present invention is:
[0010] A lithium ion battery is provided.
[0011] A second aspect of the present invention is:
[0012] Provided is a method for preparing a lithium ion battery.
[0013] Specifically, the technical solution adopted according to the first aspect of the present invention is:
[0014] A lithium ion battery, comprising a negative electrode and an electrolyte;
[0015] The negative electrode comprises a negative electrode material, and the negative electrode material is a core-shell structure, comprising a matrix and a coating layer;
[0016] The coating layer completely or partially covers the substrate;
[0017] The coating layer comprises LiF, Li3N, Li3PO4, Li2B4O7, Li4Ti5O 12 At least one of .
[0018] According to the embodiments of the present invention, one of the technical solutions has at least one of the following advantages or beneficial effects:
[0019] The negative electrode material in the lithium ion battery of the present invention comprises a coating layer. The coating layer has a good effect of inhibiting the expansion of the phosphorus material, and can inhibit the volume expansion of the phosphorus material from transferring inward rather than outward. On the other hand, the coating layer is a material with high ionic conductivity, which can improve the Li + The transfer between the phosphorus and carbon materials can better stabilize the volume expansion of the negative electrode material during the cycle; on the other hand, the coating material contains Li + , which can replenish the Li consumed during the formation process + , thereby increasing the first-week reversible capacity of the battery and improving the energy density of the battery.
[0020] According to one embodiment of the present invention, the mass ratio of the components of the coating layer to the mass ratio of the negative electrode material is 0.05%-5%. As the coating amount increases, the improvement of the battery cycle performance gradually increases, and the improvement of the cycle expansion of the lithium-ion battery also continues to improve. At the same time, the coating layer located on the surface of the negative electrode material particles reduces the contact between the negative electrode material and the electrolyte, thereby reducing the side reaction of phosphorus in the phosphorus-carbon negative electrode material and the electrolyte, further reducing the Li loss during the cycle, and improving the electrochemical performance of the battery. The present invention limits the mass ratio of the components of the coating layer to the mass ratio of the negative electrode material to 0.05%-5%. When the coating amount exceeds the above value, it will have a certain impact on the battery performance, because too much coating will cause lithium ion conduction to be blocked, and the battery performance will decrease instead.
[0021] According to one embodiment of the present invention, the mass ratio of the components of the coating layer to the mass ratio of the negative electrode material is 1%-4%.
[0022] According to one embodiment of the present invention, the components of the matrix include carbon material and phosphorus material, wherein red phosphorus has a more stable structure.
[0023] According to one embodiment of the present invention, the carbon material includes graphite.
[0024] According to one embodiment of the present invention, the phosphorus material includes at least one of red phosphorus and black phosphorus. Red phosphorus has better chemical stability and a chain structure. It can form fast ion transfer channels between the coating materials to improve the ion transfer capacity. Black phosphorus synthesis is generally difficult and has more impurities. These impurities will affect the coating effect of the coating material and cause more side reactions.
[0025] According to one embodiment of the present invention, the phosphorus material includes red phosphorus and black phosphorus in a mass ratio of 1-2:1-2.
[0026] According to one embodiment of the present invention, the coating layer comprises Li2B4O7 and Li4Ti5O in a mass ratio of 1-1.5:1-1.5. 12 Among them, Li2B4O7 provides good electrochemical stability and interface stability, which can effectively prevent electrolyte decomposition and electrochemical corrosion of electrode materials, thereby extending the cycle life of the battery. 12 With extremely low lithium ion diffusion coefficient and excellent electrochemical stability, it can effectively inhibit the growth of electrode dendrites and improve the safety and cycle life of batteries. 12 The combination of can more comprehensively inhibit the capacity decay of the phosphorus-carbon negative electrode material during the cycle, which can not only reduce the decay caused by electrolyte decomposition, but also limit the cycle expansion caused by electrode volume change. This dual effect significantly improves the cycle capacity retention rate of the battery.
[0027] According to one embodiment of the present invention, the coating layer comprises LiF and Li3PO4 in a mass ratio of 1-1.5:1-1.5. When LiF and Li3PO4 are used as coating layers in a battery, they can form a more stable and barrier interface layer. LiF can effectively inhibit the adverse reaction between the electrode material and the electrolyte, prevent the decomposition of the electrolyte and the corrosion of the electrode material. Li3PO4 can effectively control the surface chemical reaction of the electrode material and reduce its contact with the electrolyte. The combination of LiF and Li3PO4 is more effective than Li2B4O7 and Li4Ti5O 12It can provide better interface stability and chemical stability, effectively control the volume change of electrode materials and the decomposition reaction of electrolytes, thereby significantly improving the cycle capacity retention rate and cycle expansion rate of lithium-ion batteries.
[0028] The electrolyte comprises organic nitrile additives.
[0029] Although the present invention alleviates the problem of volume expansion by introducing a coating layer, the introduction of this layer inevitably leads to the problem of high temperature decomposition and generation of gas. Therefore, the present invention adds an organic nitrile additive to the electrolyte to solve this problem.
[0030] The lithium-ion battery electrolyte of the present invention contains organic nitrile additives, which interact with the negative electrode material to form an organic lithium salt with a dual protection mechanism. First, the unsaturated cyano group in the organic nitrile additive can react with the components of the coating layer to form a cyanophosphite, thereby inhibiting the reduction reaction of EC in the electrolyte. Secondly, the salt can also prevent further reaction with other lithium salts in the solvent and reduce the decomposition of lithium salts in the electrolyte. This substance is formed during the high-temperature formation process and will not decompose as the cycle proceeds.
[0031] In the lithium-ion battery of the present invention, the coordination between the negative electrode and the electrolyte not only avoids the volume expansion of the negative electrode material during the cycle, but also slows down the problems of EC reduction and lithium salt decomposition, thereby improving the cycle performance and safety of the lithium-ion battery.
[0032] The additives in the electrolyte effectively inhibit the high-temperature gas production problem, and the coating layer also reduces the corrosion of the electrolyte to the phosphorus-carbon negative electrode material. Under the synergistic effect of the two, it ensures that the gas production performance does not deteriorate during the cycle, while improving the electrochemical performance of the phosphorus-carbon negative electrode material.
[0033] The organic nitrile additive contains a cyano group. After reacting with the negative electrode material, the product formed during the lithium deintercalation process can be dissolved in the electrolyte, thereby reducing gas production. In addition, the solid / electrolyte interface film formed by the additive on the electrode surface can prevent side reactions on the electrolyte surface, thereby inhibiting gas production in the battery cell.
[0034] According to one embodiment of the present invention, the organic nitrile additive includes at least one of 1,2-adiponitrile (ADN), 1,3,6-hexanetrinitrile (HTN) and 1,3-succinonitrile (SN).
[0035] According to one embodiment of the present invention, the amount of the organic nitrile additive added is W1, the amount of the component added to the coating layer is W2, and W1 and W2 have the following relationship: 0.09<W1 / (W1+W2)<0.91.
[0036] According to one embodiment of the present invention, the ratio of W1 to W2 is 0.3-1:0.05-5.
[0037] Specifically, the technical solution adopted according to the second aspect of the present invention is:
[0038] A method for preparing the lithium ion battery comprises the following steps:
[0039] After preparing the negative electrode and the electrolyte, the components of the lithium ion battery are assembled to obtain the lithium ion battery.
[0040] According to one embodiment of the present invention, the preparation of the negative electrode comprises the following steps:
[0041] S1 takes the base material and ball-mills it to obtain a base;
[0042] S2 mixes the matrix and the coating material, and obtains the negative electrode material through a hydrothermal reaction.
[0043] According to the embodiments of the present invention, one of the technical solutions has at least one of the following advantages or beneficial effects:
[0044] The method of the present invention, firstly, can effectively control the structure and morphology of the material through ball milling and hydrothermal reaction to form a core-shell coating structure, thereby optimizing its electrochemical performance. Ball milling can not only form particles of the base material to meet structural requirements, but also refine it to increase its surface area and reaction activity; hydrothermal reaction helps to form a uniform and dense coating layer on the surface of the base, thereby improving the material's cyclic stability and long-term performance. Secondly, this method is simple and easy to implement, and is applicable to various types of base materials and coating material combinations, and has good scalability and adaptability.
[0045] According to one embodiment of the present invention, step S1 further includes the following steps: after ball milling, the obtained matrix is placed in a vacuum drying oven at 80-100°C for drying.
[0046] According to one embodiment of the present invention, the temperature of the hydrothermal reaction is 120-220°C. When the hydrothermal temperature ranges from 120°C to 220°C, as the hydrothermal temperature gradually increases, when the prepared negative electrode material is used in a lithium-ion battery, the discharge capacity and cycle capacity retention rate of the lithium-ion battery both show a trend of first increasing and then decreasing. This shows that the hydrothermal time will also have a certain effect on the electrochemical properties after coating. This is because as the hydrothermal time increases, the grain size will increase to varying degrees under high-temperature hydrothermal treatment, causing the physical properties of the granular material to change, thereby affecting the stability of the negative electrode material and the safety of the lithium-ion battery.
[0047] According to one embodiment of the present invention, the temperature of the hydrothermal reaction is 180-220°C.
[0048] According to one embodiment of the present invention, the hydrothermal reaction time is 12-24 hours.
[0049] According to one embodiment of the present invention, step S2 further includes the following steps: mixing the matrix and the coating material in anhydrous ethanol to obtain a mixture, and then performing a hydrothermal reaction.
[0050] According to one embodiment of the present invention, the method for preparing the positive electrode of the lithium ion battery comprises the following steps: mixing the positive electrode material, the conductive agent and the binder in a solvent to obtain a mixture, and coating the mixture on a metal foil to obtain the positive electrode.
[0051] According to one embodiment of the present invention, the method for preparing the negative electrode of the lithium ion battery comprises the following steps: mixing the negative electrode material of the present invention, a conductive agent, a binder, and a thickener in a solvent to obtain a mixture, and coating the mixture on a metal foil to obtain a negative electrode.
[0052] According to one embodiment of the present invention, in the method for preparing the negative electrode of the lithium ion battery, the mass ratio of the negative electrode material, the conductive agent, the binder and the thickener of the present invention is 95-100:2-3:2-3:1.
[0053] According to one embodiment of the present invention, the lithium ion battery further comprises a separator, and the separator comprises a polyethylene porous polymer film.
[0054] According to one embodiment of the present invention, the lithium-ion battery electrolyte includes a lithium salt, a non-aqueous organic solvent and an organic nitrile additive.
[0055] According to one embodiment of the present invention, the non-aqueous organic solvent includes at least one of ethylene carbonate, diethyl carbonate, propylene carbonate, propyl propionate and vinylene carbonate.
[0056] According to one embodiment of the present invention, the mass ratio of the lithium salt to the non-aqueous organic solvent is 8-10:92-95.
[0057] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practice of the present invention. DETAILED DESCRIPTION
[0058] In the description of the present invention, if there is a description of first, second, etc., it is only for the purpose of distinguishing technical features, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.
[0059] The words "preferably", "more preferably", etc. in the present invention refer to embodiments of the present invention that may provide certain beneficial effects in certain circumstances. However, other embodiments may also be preferred under the same circumstances or other circumstances. In addition, the description of one or more preferred embodiments does not imply that other embodiments are not applicable, nor is it intended to exclude other embodiments from the scope of the present invention.
[0060] When a numerical range is disclosed herein, the above range is considered to be continuous and includes the minimum and maximum values of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0061] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of the present invention.
[0062] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0063] In the embodiments and comparative examples, the positive electrode of the lithium ion battery is prepared according to the following method:
[0064] The positive electrode material lithium cobalt oxide, the conductive agent acetylene black, and the binder polyvinylidene fluoride (PVDF) are fully stirred and mixed in an N-methylpyrrolidone solvent system in a mass ratio of 98:1.2:0.8, and then coated on an Al foil. After drying, rolling, and slitting, a positive electrode sheet is obtained.
[0065] In the embodiments and comparative examples, the negative electrode sheet of the lithium ion battery is prepared according to the following method:
[0066] The negative electrode material prepared in the embodiment and the comparative example, as well as the conductive agent CNT, the binder polyacrylic acid (PAA), and the thickener sodium carboxymethyl cellulose (CMC) are fully stirred and mixed in a deionized water solvent system at a mass ratio of 95:2:2:1, and then coated on the negative electrode current collector Cu foil, and dried, cold pressed, and slit to obtain a negative electrode sheet.
[0067] In the examples and comparative examples, the separator of the lithium-ion battery is a polyethylene (PE) porous polymer film.
[0068] In the embodiments and comparative examples, the lithium ion battery was prepared according to the following method:
[0069] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is placed between the positive electrode sheet and the negative electrode sheet to play a role of safety isolation, and then wound to obtain an electrode assembly. The electrode assembly is placed in a packaging shell, and the electrolyte is injected and packaged to obtain a lithium-ion battery.
[0070] Example 1
[0071] A lithium ion battery comprises a negative electrode and an electrolyte; the electrolyte comprises an organic nitrile additive;
[0072] The negative electrode comprises a negative electrode material, and the negative electrode material is a core-shell structure, including a matrix and a coating layer;
[0073] The coating layer completely covers the substrate;
[0074] The component of the coating layer is Li3PO4.
[0075] The mass ratio of the components of the coating layer to the mass ratio of the negative electrode material is 0.05%.
[0076] The organic nitrile additive is ADN, and its mass ratio in the electrolyte is 0.5%.
[0077] The above electrolyte is prepared by the following method:
[0078] A solution prepared by mixing lithium salt LiPF6 and non-aqueous organic solvent (ethylene carbonate (EC): diethyl carbonate (DEC): propylene carbonate (PC): propyl propionate (PP): vinylene carbonate (VC)) = 20:30:20:28:2, mass ratio) in a mass ratio of 8:92, in which nitrile additives account for 0.5% of the total amount, is used as an electrolyte for a lithium ion battery.
[0079] The method for preparing the above-mentioned negative electrode material comprises the following steps:
[0080] S1: Red phosphorus and graphite were mixed in a mass ratio of 1:1 and dissolved in 100 mL of deionized water, stirred evenly, and ball-milled at a speed of 500 rpm for 2 h. After filtering and washing, the product was placed in a vacuum drying oven at 80°C and dried overnight to obtain a matrix material.
[0081] S2 adds 0.05% by mass of Li3PO4 (the mass of Li3PO4 accounts for the mass percentage of Li3PO4 and the mass percentage of the matrix material) to the matrix material, and then adds 100mL of anhydrous ethanol as a dispersant, stirs evenly to obtain a mixture, pours the above mixture into a hydrothermal reactor, and places the hydrothermal reactor into an electric constant temperature blast drying oven, and performs hydrothermal reaction at 200°C for 20 hours to obtain the above negative electrode material.
[0082] The preparation of the above battery comprises the following steps:
[0083] After preparing the positive electrode and the electrolyte, the components of the lithium ion battery are assembled to obtain the above lithium ion battery.
[0084] Example 2
[0085] The difference between Example 2 and Example 1 is that in step S2 of Example 2, 0.1 mass % of Li3PO4 is added to the base material.
[0086] Specific:
[0087] A lithium ion battery comprises a negative electrode and an electrolyte; the electrolyte comprises an organic nitrile additive;
[0088] The negative electrode comprises a negative electrode material, and the negative electrode material is a core-shell structure, including a matrix and a coating layer;
[0089] The coating layer completely covers the substrate;
[0090] The component of the coating layer is Li3PO4.
[0091] The mass ratio of the components of the coating layer to the mass ratio of the negative electrode material is 0.1%.
[0092] The organic nitrile additive is ADN, and its mass ratio in the electrolyte is 0.5%.
[0093] The above electrolyte is prepared by the following method:
[0094] A solution prepared by mixing lithium salt LiPF6 and non-aqueous organic solvent (ethylene carbonate (EC): diethyl carbonate (DEC): propylene carbonate (PC): propyl propionate (PP): vinylene carbonate (VC)) = 20:30:20:28:2, mass ratio) in a mass ratio of 8:92, in which nitrile additives account for 0.5% of the total amount, is used as an electrolyte for a lithium ion battery.
[0095] The method for preparing the above-mentioned negative electrode material comprises the following steps:
[0096] S1: Red phosphorus and graphite were mixed in a mass ratio of 1:1 and dissolved in 100 mL of deionized water, stirred evenly, and ball-milled at a speed of 500 rpm for 2 h. After filtering and washing, the product was placed in a vacuum drying oven at 80°C and dried overnight to obtain a matrix material.
[0097] S2: Add 0.1% by mass of Li3PO4 (the mass of Li3PO4 accounts for the mass percentage of Li3PO4 and the mass of the matrix material) to the matrix material, and then add 100mL of anhydrous ethanol as a dispersant, stir evenly to obtain a mixture, pour the above mixture into a hydrothermal reactor, put the hydrothermal reactor into an electric constant temperature blast drying oven, and perform hydrothermal reaction at 200°C for 20 hours to obtain the above negative electrode material.
[0098] The preparation of the above battery comprises the following steps:
[0099] After preparing the positive electrode and the electrolyte, the components of the lithium ion battery are assembled to obtain the above lithium ion battery.
[0100] Example 3
[0101] The difference between Example 3 and Example 1 is that in step S2 of Example 3, 0.4 mass% of Li3PO4 is added to the base material.
[0102] Specific:
[0103] A lithium ion battery comprises a negative electrode and an electrolyte; the electrolyte comprises an organic nitrile additive;
[0104] The negative electrode comprises a negative electrode material, and the negative electrode material is a core-shell structure, including a matrix and a coating layer;
[0105] The coating layer completely covers the substrate;
[0106] The component of the coating layer is Li3PO4.
[0107] The mass ratio of the components of the coating layer to the mass ratio of the negative electrode material is 0.4%.
[0108] The organic nitrile additive is ADN, and its mass ratio in the electrolyte is 0.5%.
[0109] The above electrolyte is prepared by the following method:
[0110] A solution prepared by mixing lithium salt LiPF6 and non-aqueous organic solvent (ethylene carbonate (EC): diethyl carbonate (DEC): propylene carbonate (PC): propyl propionate (PP): vinylene carbonate (VC)) = 20:30:20:28:2, mass ratio) in a mass ratio of 8:92, in which nitrile additives account for 0.5% of the total amount, is used as an electrolyte for a lithium ion battery.
[0111] The method for preparing the above-mentioned negative electrode material comprises the following steps:
[0112] S1: Red phosphorus and graphite were mixed in a mass ratio of 1:1 and dissolved in 100 mL of deionized water, stirred evenly, and ball-milled at a speed of 500 rpm for 2 h. After filtering and washing, the product was placed in a vacuum drying oven at 80°C and dried overnight to obtain a matrix material.
[0113] S2 adds 0.4% by mass of Li3PO4 (the mass of Li3PO4 accounts for the mass percentage of Li3PO4 and the mass percentage of the matrix material) to the matrix material, and then adds 100mL of anhydrous ethanol as a dispersant, stirs evenly to obtain a mixture, pours the above mixture into a hydrothermal reactor, and places the hydrothermal reactor into an electric constant temperature blast drying oven, and performs hydrothermal reaction at 200°C for 20 hours to obtain the above negative electrode material.
[0114] The preparation of the above battery comprises the following steps:
[0115] After preparing the positive electrode and the electrolyte, the components of the lithium ion battery are assembled to obtain the above lithium ion battery.
[0116] Example 4
[0117] The difference between Example 4 and Example 1 is that in step S2 of Example 4, 0.7 mass % of Li3PO4 is added to the base material.
[0118] Specific:
[0119] A lithium ion battery comprises a negative electrode and an electrolyte; the electrolyte comprises an organic nitrile additive;
[0120] The negative electrode comprises a negative electrode material, and the negative electrode material is a core-shell structure, including a matrix and a coating layer;
[0121] The coating layer completely covers the substrate;
[0122] The component of the coating layer is Li3PO4.
[0123] The mass ratio of the components of the coating layer to the mass ratio of the negative electrode material is 0.7%.
[0124] The organic nitrile additive is ADN, and its mass ratio in the electrolyte is 0.5%.
[0125] The above electrolyte is prepared by the following method:
[0126] A solution prepared by mixing lithium salt LiPF6 and non-aqueous organic solvent (ethylene carbonate (EC): diethyl carbonate (DEC): propylene carbonate (PC): propyl propionate (PP): vinylene carbonate (VC)) = 20:30:20:28:2, mass ratio) in a mass ratio of 8:92, in which nitrile additives account for 0.5% of the total amount, is used as an electrolyte for a lithium ion battery.
[0127] The method for preparing the above-mentioned negative electrode material comprises the following steps:
[0128] S1: Red phosphorus and graphite were mixed in a mass ratio of 1:1 and dissolved in 100 mL of deionized water, stirred evenly, and ball-milled at a speed of 500 rpm for 2 h. After filtering and washing, the product was placed in a vacuum drying oven at 80°C and dried overnight to obtain a matrix material.
[0129] S2 adds 0.7% by mass of Li3PO4 (the mass of Li3PO4 accounts for the mass percentage of Li3PO4 and the mass percentage of the matrix material) to the matrix material, and then adds 100mL of anhydrous ethanol as a dispersant, stirs evenly to obtain a mixture, pours the above mixture into a hydrothermal reactor, and places the hydrothermal reactor into an electric constant temperature blast drying oven, and performs hydrothermal reaction at 200°C for 20 hours to obtain the above negative electrode material.
[0130] The preparation of the above battery comprises the following steps:
[0131] After preparing the positive electrode and the electrolyte, the components of the lithium ion battery are assembled to obtain the above lithium ion battery.
[0132] Example 5
[0133] The difference between Example 5 and Example 1 is that in step S2 of Example 5, 1.0 mass % of Li3PO4 is added to the base material.
[0134] Specific:
[0135] A lithium ion battery comprises a negative electrode and an electrolyte; the electrolyte comprises an organic nitrile additive;
[0136] The negative electrode comprises a negative electrode material, and the negative electrode material is a core-shell structure, including a matrix and a coating layer;
[0137] The coating layer completely covers the substrate;
[0138] The component of the coating layer is Li3PO4.
[0139] The mass ratio of the components of the coating layer to the mass ratio of the negative electrode material is 1.0%.
[0140] The organic nitrile additive is ADN, and its mass ratio in the electrolyte is 0.5%.
[0141] The above electrolyte is prepared by the following method:
[0142] A solution prepared by mixing lithium salt LiPF6 and non-aqueous organic solvent (ethylene carbonate (EC): diethyl carbonate (DEC): propylene carbonate (PC): propyl propionate (PP): vinylene carbonate (VC)) = 20:30:20:28:2, mass ratio) in a mass ratio of 8:92, in which nitrile additives account for 0.5% of the total amount, is used as an electrolyte for a lithium ion battery.
[0143] The method for preparing the above-mentioned negative electrode material comprises the following steps:
[0144] S1: Red phosphorus and graphite were mixed in a mass ratio of 1:1 and dissolved in 100 mL of deionized water, stirred evenly, and ball-milled at a speed of 500 rpm for 2 h. After filtering and washing, the product was placed in a vacuum drying oven at 80°C and dried overnight to obtain a matrix material.
[0145] S2: Add 1.0% by mass of Li3PO4 (the mass of Li3PO4 accounts for the mass percentage of Li3PO4 and the mass percentage of the matrix material) to the matrix material, and then add 100mL of anhydrous ethanol as a dispersant, stir evenly to obtain a mixture, pour the above mixture into a hydrothermal reactor, put the hydrothermal reactor into an electric constant temperature blast drying oven, and perform hydrothermal reaction at 200°C for 20 hours to obtain the above negative electrode material.
[0146] The preparation of the above battery comprises the following steps:
[0147] After preparing the positive electrode and the electrolyte, the components of the lithium ion battery are assembled to obtain the above lithium ion battery.
[0148] Example 6
[0149] The difference between Example 6 and Example 1 is that in step S2 of Example 6, 2.0 mass % of Li3PO4 is added to the base material.
[0150] Specific:
[0151] A lithium ion battery comprises a negative electrode and an electrolyte; the electrolyte comprises an organic nitrile additive;
[0152] The negative electrode comprises a negative electrode material, and the negative electrode material is a core-shell structure, including a matrix and a coating layer;
[0153] The coating layer completely covers the substrate;
[0154] The component of the coating layer is Li3PO4.
[0155] The mass ratio of the components of the coating layer to the mass ratio of the negative electrode material is 2.0%.
[0156] The organic nitrile additive is ADN, and its mass ratio in the electrolyte is 0.5%.
[0157] The above electrolyte is prepared by the following method:
[0158] A solution prepared by mixing lithium salt LiPF6 and non-aqueous organic solvent (ethylene carbonate (EC): diethyl carbonate (DEC): propylene carbonate (PC): propyl propionate (PP): vinylene carbonate (VC)) = 20:30:20:28:2, mass ratio) in a mass ratio of 8:92, in which nitrile additives account for 0.5% of the total amount, is used as an electrolyte for a lithium ion battery.
[0159] The method for preparing the above-mentioned negative electrode material comprises the following steps:
[0160] S1: Red phosphorus and graphite were mixed in a mass ratio of 1:1 and dissolved in 100 mL of deionized water, stirred evenly, and ball-milled at a speed of 500 rpm for 2 h. After filtering and washing, the product was placed in a vacuum drying oven at 80°C and dried overnight to obtain a matrix material.
[0161] S2 adds 2.0% by mass of Li3PO4 (the mass of Li3PO4 accounts for the mass percentage of Li3PO4 and the mass percentage of the matrix material) to the matrix material, and then adds 100mL of anhydrous ethanol as a dispersant, stirs evenly to obtain a mixture, pours the above mixture into a hydrothermal reactor, and places the hydrothermal reactor into an electric constant temperature blast drying oven, and performs hydrothermal reaction at 200°C for 20 hours to obtain the above negative electrode material.
[0162] The preparation of the above battery comprises the following steps:
[0163] After preparing the positive electrode and the electrolyte, the components of the lithium ion battery are assembled to obtain the above lithium ion battery.
[0164] Example 7
[0165] The difference between Example 7 and Example 1 is that in step S2 of Example 7, 3.0 mass % of Li3PO4 is added to the base material.
[0166] Specific:
[0167] A lithium ion battery comprises a negative electrode and an electrolyte; the electrolyte comprises an organic nitrile additive;
[0168] The negative electrode comprises a negative electrode material, and the negative electrode material is a core-shell structure, including a matrix and a coating layer;
[0169] The coating layer completely covers the substrate;
[0170] The component of the coating layer is Li3PO4.
[0171] The mass ratio of the components of the coating layer to the mass ratio of the negative electrode material is 3.0%.
[0172] The organic nitrile additive is ADN, and its mass ratio in the electrolyte is 0.5%.
[0173] The above electrolyte is prepared by the following method:
[0174] A solution prepared by mixing lithium salt LiPF6 and non-aqueous organic solvent (ethylene carbonate (EC): diethyl carbonate (DEC): propylene carbonate (PC): propyl propionate (PP): vinylene carbonate (VC)) = 20:30:20:28:2, mass ratio) in a mass ratio of 8:92, in which nitrile additives account for 0.5% of the total amount, is used as an electrolyte for a lithium ion battery.
[0175] The method for preparing the above-mentioned negative electrode material comprises the following steps:
[0176] S1: Red phosphorus and graphite were mixed in a mass ratio of 1:1 and dissolved in 100 mL of deionized water, stirred evenly, and ball-milled at a speed of 500 rpm for 2 h. After filtering and washing, the product was placed in a vacuum drying oven at 80°C and dried overnight to obtain a matrix material.
[0177] S2 adds 3.0% by mass of Li3PO4 (the mass of Li3PO4 accounts for the mass percentage of Li3PO4 and the mass percentage of the matrix material) to the matrix material, and then adds 100mL of anhydrous ethanol as a dispersant, stirs evenly to obtain a mixture, pours the above mixture into a hydrothermal reactor, and places the hydrothermal reactor into an electric constant temperature blast drying oven, and performs hydrothermal reaction at 200°C for 20 hours to obtain the above negative electrode material.
[0178] The preparation of the above battery comprises the following steps:
[0179] After preparing the positive electrode and the electrolyte, the components of the lithium ion battery are assembled to obtain the above lithium ion battery.
[0180] Example 8
[0181] The difference between Example 8 and Example 1 is that in step S2 of Example 8, 4.0 mass % of Li3PO4 is added to the base material.
[0182] Specific:
[0183] A lithium ion battery comprises a negative electrode and an electrolyte; the electrolyte comprises an organic nitrile additive;
[0184] The negative electrode comprises a negative electrode material, and the negative electrode material is a core-shell structure, including a matrix and a coating layer;
[0185] The coating layer completely covers the substrate;
[0186] The component of the coating layer is Li3PO4.
[0187] The mass ratio of the components of the coating layer to the mass ratio of the negative electrode material is 4.0%.
[0188] The organic nitrile additive is ADN, and its mass ratio in the electrolyte is 0.5%.
[0189] The above electrolyte is prepared by the following method:
[0190] A solution prepared by mixing lithium salt LiPF6 and non-aqueous organic solvent (ethylene carbonate (EC): diethyl carbonate (DEC): propylene carbonate (PC): propyl propionate (PP): vinylene carbonate (VC)) = 20:30:20:28:2, mass ratio) in a mass ratio of 8:92, in which nitrile additives account for 0.5% of the total amount, is used as an electrolyte for a lithium ion battery.
[0191] The method for preparing the above-mentioned negative electrode material comprises the following steps:
[0192] S1: Red phosphorus and graphite were mixed in a mass ratio of 1:1 and dissolved in 100 mL of deionized water, stirred evenly, and ball-milled at a speed of 500 rpm for 2 h. After filtering and washing, the product was placed in a vacuum drying oven at 80°C and dried overnight to obtain a matrix material.
[0193] S2: Add 4.0% by mass of Li3PO4 (the mass of Li3PO4 accounts for the mass percentage of Li3PO4 and the mass percentage of the matrix material) to the matrix material, and then add 100mL of anhydrous ethanol as a dispersant, stir evenly to obtain a mixture, pour the above mixture into a hydrothermal reactor, put the hydrothermal reactor into an electric constant temperature blast drying oven, and perform hydrothermal reaction at 200°C for 20 hours to obtain the above negative electrode material.
[0194] The preparation of the above battery comprises the following steps:
[0195] After preparing the positive electrode and the electrolyte, the components of the lithium ion battery are assembled to obtain the above lithium ion battery.
[0196] Example 9
[0197] The difference between Example 9 and Example 1 is that in step S2 of Example 9, 5.0 mass % of Li3PO4 is added to the base material.
[0198] Specific:
[0199] A lithium ion battery comprises a negative electrode and an electrolyte; the electrolyte comprises an organic nitrile additive;
[0200] The negative electrode comprises a negative electrode material, and the negative electrode material is a core-shell structure, including a matrix and a coating layer;
[0201] The coating layer completely covers the substrate;
[0202] The component of the coating layer is Li3PO4.
[0203] The mass ratio of the components of the coating layer to the mass ratio of the negative electrode material is 5.0%.
[0204] The organic nitrile additive is ADN, and its mass ratio in the electrolyte is 0.5%.
[0205] The above electrolyte is prepared by the following method:
[0206] A solution prepared by mixing lithium salt LiPF6 and non-aqueous organic solvent (ethylene carbonate (EC): diethyl carbonate (DEC): propylene carbonate (PC): propyl propionate (PP): vinylene carbonate (VC)) = 20:30:20:28:2, mass ratio) in a mass ratio of 8:92, in which nitrile additives account for 0.5% of the total amount, is used as an electrolyte for a lithium ion battery.
[0207] The method for preparing the above-mentioned negative electrode material comprises the following steps:
[0208] S1: Red phosphorus and graphite were mixed in a mass ratio of 1:1 and dissolved in 100 mL of deionized water, stirred evenly, and ball-milled at a speed of 500 rpm for 2 h. After filtering and washing, the product was placed in a vacuum drying oven at 80°C and dried overnight to obtain a matrix material.
[0209] S2 adds 5.0% by mass of Li3PO4 (the mass of Li3PO4 accounts for the mass percentage of Li3PO4 and the mass of the matrix material) to the matrix material, and then adds 100mL of anhydrous ethanol as a dispersant, stirs evenly to obtain a mixture, pours the above mixture into a hydrothermal reactor, and places the hydrothermal reactor into an electric constant temperature blast drying oven, and performs hydrothermal reaction at 200°C for 20 hours to obtain the above negative electrode material.
[0210] The preparation of the above battery comprises the following steps:
[0211] After preparing the positive electrode and the electrolyte, the components of the lithium ion battery are assembled to obtain the above lithium ion battery.
[0212] Example 10
[0213] The difference between Example 10 and Example 7 is that in step S2 of Example 10, the hydrothermal reaction temperature is 180°C.
[0214] Specific:
[0215] A lithium ion battery comprises a negative electrode and an electrolyte; the electrolyte comprises an organic nitrile additive;
[0216] The negative electrode comprises a negative electrode material, and the negative electrode material is a core-shell structure, including a matrix and a coating layer;
[0217] The coating layer completely covers the substrate;
[0218] The component of the coating layer is Li3PO4.
[0219] The mass ratio of the components of the coating layer to the mass ratio of the negative electrode material is 3.0%.
[0220] The organic nitrile additive is ADN, and its mass ratio in the electrolyte is 0.5%.
[0221] The above electrolyte is prepared by the following method:
[0222] A solution prepared by mixing lithium salt LiPF6 and non-aqueous organic solvent (ethylene carbonate (EC): diethyl carbonate (DEC): propylene carbonate (PC): propyl propionate (PP): vinylene carbonate (VC)) = 20:30:20:28:2, mass ratio) in a mass ratio of 8:92, in which nitrile additives account for 0.5% of the total amount, is used as an electrolyte for a lithium ion battery.
[0223] The method for preparing the above-mentioned negative electrode material comprises the following steps:
[0224] S1: Red phosphorus and graphite were mixed in a mass ratio of 1:1 and dissolved in 100 mL of deionized water, stirred evenly, and ball-milled at a speed of 500 rpm for 2 h. After filtering and washing, the product was placed in a vacuum drying oven at 80°C and dried overnight to obtain a matrix material.
[0225] S2: Add 3.0% by mass of Li3PO4 (the mass of Li3PO4 accounts for the mass percentage of Li3PO4 and the mass of the matrix material) to the matrix material, and then add 100mL of anhydrous ethanol as a dispersant, stir evenly to obtain a mixture, pour the above mixture into a hydrothermal reactor, put the hydrothermal reactor into an electric constant temperature blast drying oven, and perform hydrothermal reaction at 180°C for 20 hours to obtain the above negative electrode material.
[0226] The preparation of the above battery comprises the following steps:
[0227] After preparing the positive electrode and the electrolyte, the components of the lithium ion battery are assembled to obtain the above lithium ion battery.
[0228] Embodiment 11
[0229] The difference between Example 11 and Example 7 is that in step S2 of Example 11, the hydrothermal reaction temperature is 220°C.
[0230] Specific:
[0231] A lithium ion battery comprises a negative electrode and an electrolyte; the electrolyte comprises an organic nitrile additive;
[0232] The negative electrode comprises a negative electrode material, and the negative electrode material is a core-shell structure, including a matrix and a coating layer;
[0233] The coating layer completely covers the substrate;
[0234] The component of the coating layer is Li3PO4.
[0235] The mass ratio of the components of the coating layer to the mass ratio of the negative electrode material is 3.0%.
[0236] The organic nitrile additive is ADN, and its mass ratio in the electrolyte is 0.5%.
[0237] The above electrolyte is prepared by the following method:
[0238] A solution prepared by mixing lithium salt LiPF6 and non-aqueous organic solvent (ethylene carbonate (EC): diethyl carbonate (DEC): propylene carbonate (PC): propyl propionate (PP): vinylene carbonate (VC)) = 20:30:20:28:2, mass ratio) in a mass ratio of 8:92, in which nitrile additives account for 0.5% of the total amount, is used as an electrolyte for a lithium ion battery.
[0239] The method for preparing the above-mentioned negative electrode material comprises the following steps:
[0240] S1: Red phosphorus and graphite were mixed in a mass ratio of 1:1 and dissolved in 100 mL of deionized water, stirred evenly, and ball-milled at a speed of 500 rpm for 2 h. After filtering and washing, the product was placed in a vacuum drying oven at 80°C and dried overnight to obtain a matrix material.
[0241] S2: Add 3.0% by mass of Li3PO4 (the mass of Li3PO4 accounts for the mass percentage of Li3PO4 and the mass of the matrix material) to the matrix material, and then add 100 mL of anhydrous ethanol as a dispersant, stir evenly to obtain a mixture, pour the above mixture into a hydrothermal reactor, put the hydrothermal reactor into an electric constant temperature blast drying oven, and perform hydrothermal reaction at 220°C for 20 hours to obtain the above negative electrode material.
[0242] The preparation of the above battery comprises the following steps:
[0243] After preparing the positive electrode and the electrolyte, the components of the lithium ion battery are assembled to obtain the above lithium ion battery.
[0244] Example 12
[0245] The difference between Example 12 and Example 7 is that in step S1 of Example 12, the components of the matrix material are black phosphorus and graphite in a mass ratio of 1:1.
[0246] Specific:
[0247] A lithium ion battery comprises a negative electrode and an electrolyte; the electrolyte comprises an organic nitrile additive;
[0248] The negative electrode comprises a negative electrode material, and the negative electrode material is a core-shell structure, including a matrix and a coating layer;
[0249] The coating layer completely covers the substrate;
[0250] The component of the coating layer is Li3PO4.
[0251] The mass ratio of the components of the coating layer to the mass ratio of the negative electrode material is 3.0%.
[0252] The organic nitrile additive is ADN, and its mass ratio in the electrolyte is 0.5%.
[0253] The above electrolyte is prepared by the following method:
[0254] A solution prepared by mixing lithium salt LiPF6 and non-aqueous organic solvent (ethylene carbonate (EC): diethyl carbonate (DEC): propylene carbonate (PC): propyl propionate (PP): vinylene carbonate (VC)) = 20:30:20:28:2, mass ratio) in a mass ratio of 8:92, in which nitrile additives account for 0.5% of the total amount, is used as an electrolyte for a lithium ion battery.
[0255] The method for preparing the above-mentioned negative electrode material comprises the following steps:
[0256] S1: Mix black phosphorus and graphite in a mass ratio of 1:1 and dissolve in 100 mL of deionized water, stir evenly, and ball-mill at a speed of 500 rpm for 2 h. After filtering and washing, the product is placed in a vacuum drying oven at 80°C and dried overnight to obtain a matrix material.
[0257] S2 adds 3.0% by mass of Li3PO4 (the mass of Li3PO4 accounts for the mass percentage of Li3PO4 and the mass percentage of the matrix material) to the matrix material, and then adds 100mL of anhydrous ethanol as a dispersant, stirs evenly to obtain a mixture, pours the above mixture into a hydrothermal reactor, and places the hydrothermal reactor into an electric constant temperature blast drying oven, and performs hydrothermal reaction at 200°C for 20 hours to obtain the above negative electrode material.
[0258] The preparation of the above battery comprises the following steps:
[0259] After preparing the positive electrode and the electrolyte, the components of the lithium ion battery are assembled to obtain the above lithium ion battery.
[0260] Example 13
[0261] The difference between Example 13 and Example 7 is that in step S2 of Example 13, the component of the coating layer is 3% by mass of LiF.
[0262] Specific:
[0263] A lithium ion battery comprises a negative electrode and an electrolyte; the electrolyte comprises an organic nitrile additive;
[0264] The negative electrode comprises a negative electrode material, and the negative electrode material is a core-shell structure, including a matrix and a coating layer;
[0265] The coating layer completely covers the substrate;
[0266] The component of the coating layer is LiF.
[0267] The mass ratio of the components of the coating layer to the mass ratio of the negative electrode material is 3.0%.
[0268] The organic nitrile additive is ADN, and its mass ratio in the electrolyte is 0.5%.
[0269] The above electrolyte is prepared by the following method:
[0270] A solution prepared by mixing lithium salt LiPF6 and non-aqueous organic solvent (ethylene carbonate (EC): diethyl carbonate (DEC): propylene carbonate (PC): propyl propionate (PP): vinylene carbonate (VC)) = 20:30:20:28:2, mass ratio) in a mass ratio of 8:92, in which nitrile additives account for 0.5% of the total amount, is used as an electrolyte for a lithium ion battery.
[0271] The method for preparing the above-mentioned negative electrode material comprises the following steps:
[0272] S1: Red phosphorus and graphite were mixed in a mass ratio of 1:1 and dissolved in 100 mL of deionized water, stirred evenly, and ball-milled at a speed of 500 rpm for 2 h. After filtering and washing, the product was placed in a vacuum drying oven at 80°C and dried overnight to obtain a matrix material.
[0273] S2: Add 3.0% by mass of LiF (the mass of LiF accounts for the mass percentage of LiF and the mass of the matrix material) to the matrix material, and then add 100 mL of anhydrous ethanol as a dispersant, stir evenly to obtain a mixture, pour the above mixture into a hydrothermal reactor, put the hydrothermal reactor into an electric constant temperature blast drying oven, and perform hydrothermal reaction at 200°C for 20 hours to obtain the above negative electrode material.
[0274] The preparation of the above battery comprises the following steps:
[0275] After preparing the positive electrode and the electrolyte, the components of the lithium ion battery are assembled to obtain the above lithium ion battery.
[0276] Embodiment 14
[0277] The difference between Example 14 and Example 7 is that in step S2 of Example 14, the component of the coating layer is 3% by mass of Li3N.
[0278] Specific:
[0279] A lithium ion battery comprises a negative electrode and an electrolyte; the electrolyte comprises an organic nitrile additive;
[0280] The negative electrode comprises a negative electrode material, and the negative electrode material is a core-shell structure, including a matrix and a coating layer;
[0281] The coating layer completely covers the substrate;
[0282] The component of the coating layer is Li3N.
[0283] The mass ratio of the components of the coating layer to the mass ratio of the negative electrode material is 3.0%.
[0284] The organic nitrile additive is ADN, and its mass ratio in the electrolyte is 0.5%.
[0285] The above electrolyte is prepared by the following method:
[0286] A solution prepared by mixing lithium salt LiPF6 and non-aqueous organic solvent (ethylene carbonate (EC): diethyl carbonate (DEC): propylene carbonate (PC): propyl propionate (PP): vinylene carbonate (VC)) = 20:30:20:28:2, mass ratio) in a mass ratio of 8:92, in which nitrile additives account for 0.5% of the total amount, is used as an electrolyte for a lithium ion battery.
[0287] The method for preparing the above-mentioned negative electrode material comprises the following steps:
[0288] S1: Red phosphorus and graphite were mixed in a mass ratio of 1:1 and dissolved in 100 mL of deionized water, stirred evenly, and ball-milled at a speed of 500 rpm for 2 h. After filtering and washing, the product was placed in a vacuum drying oven at 80°C and dried overnight to obtain a matrix material.
[0289] S2: Add 3.0% by mass of Li3N (the mass of Li3N accounts for the mass percentage of Li3N and the mass percentage of the matrix material) to the matrix material, and then add 100 mL of anhydrous ethanol as a dispersant, stir evenly to obtain a mixture, pour the above mixture into a hydrothermal reactor, put the hydrothermal reactor into an electric constant temperature blast drying oven, and perform hydrothermal reaction at 200°C for 20 hours to obtain the above negative electrode material.
[0290] The preparation of the above battery comprises the following steps:
[0291] After preparing the positive electrode and the electrolyte, the components of the lithium ion battery are assembled to obtain the above lithium ion battery.
[0292] Embodiment 15
[0293] The difference between Example 15 and Example 7 is that in step S2 of Example 15, the components of the coating layer are 1.5% by mass of LiF and 1.5% by mass of Li3PO4.
[0294] Specific:
[0295] A lithium ion battery comprises a negative electrode and an electrolyte; the electrolyte comprises an organic nitrile additive;
[0296] The negative electrode comprises a negative electrode material, and the negative electrode material is a core-shell structure, including a matrix and a coating layer;
[0297] The coating layer completely covers the substrate;
[0298] The components of the coating layer are LiF and Li3PO4.
[0299] The mass ratio of the components of the coating layer to the mass ratio of the negative electrode material is 3.0%.
[0300] The organic nitrile additive is ADN, and its mass ratio in the electrolyte is 0.5%.
[0301] The above electrolyte is prepared by the following method:
[0302] A solution prepared by mixing lithium salt LiPF6 and non-aqueous organic solvent (ethylene carbonate (EC): diethyl carbonate (DEC): propylene carbonate (PC): propyl propionate (PP): vinylene carbonate (VC)) = 20:30:20:28:2, mass ratio) in a mass ratio of 8:92, in which nitrile additives account for 0.5% of the total amount, is used as an electrolyte for a lithium ion battery.
[0303] The method for preparing the above-mentioned negative electrode material comprises the following steps:
[0304] S1: Red phosphorus and graphite were mixed in a mass ratio of 1:1 and dissolved in 100 mL of deionized water, stirred evenly, and ball-milled at a speed of 500 rpm for 2 h. After filtering and washing, the product was placed in a vacuum drying oven at 80°C and dried overnight to obtain a matrix material.
[0305] S2: Add 1.5% by mass of LiF and 1.5% by mass of Li3PO4 (the mass of LiF and Li3PO4 accounts for the mass of LiF and Li3PO4 and the mass of the matrix material) to the matrix material, then add 100 mL of anhydrous ethanol as a dispersant, stir evenly to obtain a mixture, pour the above mixture into a hydrothermal reactor, put the hydrothermal reactor into an electric constant temperature blast drying oven, and perform hydrothermal reaction at 200°C for 20 hours to obtain the above negative electrode material.
[0306] The preparation of the above battery comprises the following steps:
[0307] After preparing the positive electrode and the electrolyte, the components of the lithium ion battery are assembled to obtain the above lithium ion battery.
[0308] Example 16
[0309] The difference between Example 16 and Example 7 is that in step S2 of Example 16, the coating layer comprises 1.5% by mass of Li2B4O7 and 1.5% by mass of Li4Ti5O 12 .
[0310] Specific:
[0311] A lithium ion battery comprises a negative electrode and an electrolyte; the electrolyte comprises an organic nitrile additive;
[0312] The negative electrode comprises a negative electrode material, and the negative electrode material is a core-shell structure, including a matrix and a coating layer;
[0313] The coating layer completely covers the substrate;
[0314] The coating layer is composed of Li2B4O7 and Li4Ti5O 12 .
[0315] The mass ratio of the components of the coating layer to the mass ratio of the negative electrode material is 3.0%.
[0316] The organic nitrile additive is ADN, and its mass ratio in the electrolyte is 0.5%.
[0317] The above electrolyte is prepared by the following method:
[0318] A solution prepared by mixing lithium salt LiPF6 and non-aqueous organic solvent (ethylene carbonate (EC): diethyl carbonate (DEC): propylene carbonate (PC): propyl propionate (PP): vinylene carbonate (VC)) = 20:30:20:28:2, mass ratio) in a mass ratio of 8:92, in which nitrile additives account for 0.5% of the total amount, is used as an electrolyte for a lithium ion battery.
[0319] The method for preparing the above-mentioned negative electrode material comprises the following steps:
[0320] S1: Red phosphorus and graphite were mixed in a mass ratio of 1:1 and dissolved in 100 mL of deionized water, stirred evenly, and ball-milled at a speed of 500 rpm for 2 h. After filtering and washing, the product was placed in a vacuum drying oven at 80°C and dried overnight to obtain a matrix material.
[0321] S2 adds 1.5% by mass of Li2B4O7 and 1.5% by mass of Li4Ti5O 12 (Li2B4O7 and Li4Ti5O 12 mass, accounting for Li2B4O7 and Li4Ti5O 12 The mixture was poured into a hydrothermal reaction kettle, and the hydrothermal reaction kettle was placed in an electric constant temperature blast drying oven for hydrothermal reaction at 200° C. for 20 h to obtain the above-mentioned negative electrode material.
[0322] The preparation of the above battery comprises the following steps:
[0323] After preparing the positive electrode and the electrolyte, the components of the lithium ion battery are assembled to obtain the above lithium ion battery.
[0324] Embodiment 17
[0325] The difference between Example 17 and Example 7 is that the nitrile additive in the electrolyte of Example 17 is HTN.
[0326] Specific:
[0327] A lithium ion battery comprises a negative electrode and an electrolyte; the electrolyte comprises an organic nitrile additive;
[0328] The negative electrode comprises a negative electrode material, and the negative electrode material is a core-shell structure, including a matrix and a coating layer;
[0329] The coating layer completely covers the substrate;
[0330] The component of the coating layer is Li3PO4.
[0331] The mass ratio of the components of the coating layer to the mass ratio of the negative electrode material is 3.0%.
[0332] The organic nitrile additive is HTN, and its mass ratio in the electrolyte is 0.5%.
[0333] The above electrolyte is prepared by the following method:
[0334] A solution prepared by mixing lithium salt LiPF6 and non-aqueous organic solvent (ethylene carbonate (EC): diethyl carbonate (DEC): propylene carbonate (PC): propyl propionate (PP): vinylene carbonate (VC)) = 20:30:20:28:2, mass ratio) in a mass ratio of 8:92, in which nitrile additives account for 0.5% of the total amount, is used as an electrolyte for a lithium ion battery.
[0335] The method for preparing the above-mentioned negative electrode material comprises the following steps:
[0336] S1: Red phosphorus and graphite were mixed in a mass ratio of 1:1 and dissolved in 100 mL of deionized water, stirred evenly, and ball-milled at a speed of 500 rpm for 2 h. After filtering and washing, the product was placed in a vacuum drying oven at 80°C and dried overnight to obtain a matrix material.
[0337] S2 adds 3.0% by mass of Li3PO4 (the mass of Li3PO4 accounts for the mass percentage of Li3PO4 and the mass percentage of the matrix material) to the matrix material, and then adds 100mL of anhydrous ethanol as a dispersant, stirs evenly to obtain a mixture, pours the above mixture into a hydrothermal reactor, and places the hydrothermal reactor into an electric constant temperature blast drying oven, and performs hydrothermal reaction at 200°C for 20 hours to obtain the above negative electrode material.
[0338] The preparation of the above battery comprises the following steps:
[0339] After preparing the positive electrode and the electrolyte, the components of the lithium ion battery are assembled to obtain the above lithium ion battery.
[0340] Embodiment 18
[0341] The difference between Example 18 and Example 7 is that the nitrile additive in the electrolyte of Example 18 is SN.
[0342] Specific:
[0343] A lithium ion battery comprises a negative electrode and an electrolyte; the electrolyte comprises an organic nitrile additive;
[0344] The negative electrode comprises a negative electrode material, and the negative electrode material is a core-shell structure, including a matrix and a coating layer;
[0345] The coating layer completely covers the substrate;
[0346] The component of the coating layer is Li3PO4.
[0347] The mass ratio of the components of the coating layer to the mass ratio of the negative electrode material is 3.0%.
[0348] The organic nitrile additive is SN, and its mass ratio in the electrolyte is 0.5%.
[0349] The above electrolyte is prepared by the following method:
[0350] A solution prepared by mixing lithium salt LiPF6 and non-aqueous organic solvent (ethylene carbonate (EC): diethyl carbonate (DEC): propylene carbonate (PC): propyl propionate (PP): vinylene carbonate (VC)) = 20:30:20:28:2, mass ratio) in a mass ratio of 8:92, in which nitrile additives account for 0.5% of the total amount, is used as an electrolyte for a lithium ion battery.
[0351] The method for preparing the above-mentioned negative electrode material comprises the following steps:
[0352] S1: Red phosphorus and graphite were mixed in a mass ratio of 1:1 and dissolved in 100 mL of deionized water, stirred evenly, and ball-milled at a speed of 500 rpm for 2 h. After filtering and washing, the product was placed in a vacuum drying oven at 80°C and dried overnight to obtain a matrix material.
[0353] S2 adds 3.0% by mass of Li3PO4 (the mass of Li3PO4 accounts for the mass percentage of Li3PO4 and the mass percentage of the matrix material) to the matrix material, and then adds 100mL of anhydrous ethanol as a dispersant, stirs evenly to obtain a mixture, pours the above mixture into a hydrothermal reactor, and places the hydrothermal reactor into an electric constant temperature blast drying oven, and performs hydrothermal reaction at 200°C for 20 hours to obtain the above negative electrode material.
[0354] The preparation of the above battery comprises the following steps:
[0355] After preparing the positive electrode and the electrolyte, the components of the lithium ion battery are assembled to obtain the above lithium ion battery.
[0356] Embodiment 19
[0357] The difference between Example 19 and Example 7 is that the content of nitrile additive in the electrolyte of Example 19 is 0.3%.
[0358] Specific:
[0359] A lithium ion battery comprises a negative electrode and an electrolyte; the electrolyte comprises an organic nitrile additive;
[0360] The negative electrode comprises a negative electrode material, and the negative electrode material is a core-shell structure, including a matrix and a coating layer;
[0361] The coating layer completely covers the substrate;
[0362] The component of the coating layer is Li3PO4.
[0363] The mass ratio of the components of the coating layer to the mass ratio of the negative electrode material is 3.0%.
[0364] The organic nitrile additive is ADN, and its mass ratio in the electrolyte is 0.3%.
[0365] The above electrolyte is prepared by the following method:
[0366] A solution prepared by mixing lithium salt LiPF6 and non-aqueous organic solvent (ethylene carbonate (EC): diethyl carbonate (DEC): propylene carbonate (PC): propyl propionate (PP): vinylene carbonate (VC)) = 20:30:20:28:2, mass ratio) in a mass ratio of 8:92, in which nitrile additives account for 0.3% of the total amount, is used as an electrolyte for a lithium ion battery.
[0367] The method for preparing the above-mentioned negative electrode material comprises the following steps:
[0368] S1: Red phosphorus and graphite were mixed in a mass ratio of 1:1 and dissolved in 100 mL of deionized water, stirred evenly, and ball-milled at a speed of 500 rpm for 2 h. After filtering and washing, the product was placed in a vacuum drying oven at 80°C and dried overnight to obtain a matrix material.
[0369] S2 adds 3.0% by mass of Li3PO4 (the mass of Li3PO4 accounts for the mass percentage of Li3PO4 and the mass percentage of the matrix material) to the matrix material, and then adds 100mL of anhydrous ethanol as a dispersant, stirs evenly to obtain a mixture, pours the above mixture into a hydrothermal reactor, and places the hydrothermal reactor into an electric constant temperature blast drying oven, and performs hydrothermal reaction at 200°C for 20 hours to obtain the above negative electrode material.
[0370] The preparation of the above battery comprises the following steps:
[0371] After preparing the positive electrode and the electrolyte, the components of the lithium ion battery are assembled to obtain the above lithium ion battery.
[0372] Embodiment 20
[0373] The difference between Example 20 and Example 7 is that the content of nitrile additives in the electrolyte of Example 20 is 1%.
[0374] Specific:
[0375] A lithium ion battery comprises a negative electrode and an electrolyte; the electrolyte comprises an organic nitrile additive;
[0376] The negative electrode comprises a negative electrode material, and the negative electrode material is a core-shell structure, including a matrix and a coating layer;
[0377] The coating layer completely covers the substrate;
[0378] The component of the coating layer is Li3PO4.
[0379] The mass ratio of the components of the coating layer to the mass ratio of the negative electrode material is 3.0%.
[0380] The organic nitrile additive is ADN, and its mass ratio in the electrolyte is 1%.
[0381] The above electrolyte is prepared by the following method:
[0382] A solution prepared by mixing lithium salt LiPF6 and non-aqueous organic solvent (ethylene carbonate (EC): diethyl carbonate (DEC): propylene carbonate (PC): propyl propionate (PP): vinylene carbonate (VC)) = 20:30:20:28:2, mass ratio) in a mass ratio of 8:92, in which nitrile additives account for 1% of the total amount, is used as an electrolyte for a lithium ion battery.
[0383] The method for preparing the above-mentioned negative electrode material comprises the following steps:
[0384] S1: Red phosphorus and graphite were mixed in a mass ratio of 1:1 and dissolved in 100 mL of deionized water, stirred evenly, and ball-milled at a speed of 500 rpm for 2 h. After filtering and washing, the product was placed in a vacuum drying oven at 80°C and dried overnight to obtain a matrix material.
[0385] S2 adds 3.0% by mass of Li3PO4 (the mass of Li3PO4 accounts for the mass percentage of Li3PO4 and the mass percentage of the matrix material) to the matrix material, and then adds 100mL of anhydrous ethanol as a dispersant, stirs evenly to obtain a mixture, pours the above mixture into a hydrothermal reactor, and places the hydrothermal reactor into an electric constant temperature blast drying oven, and performs hydrothermal reaction at 200°C for 20 hours to obtain the above negative electrode material.
[0386] The preparation of the above battery comprises the following steps:
[0387] After preparing the positive electrode and the electrolyte, the components of the lithium ion battery are assembled to obtain the above lithium ion battery.
[0388] Embodiment 21
[0389] The difference between Example 21 and Example 7 is that there is no nitrile additive in the electrolyte of Example 21.
[0390] Specific:
[0391] A lithium ion battery, comprising a negative electrode and an electrolyte; the electrolyte contains no organic nitrile additives;
[0392] The negative electrode comprises a negative electrode material, and the negative electrode material is a core-shell structure, including a matrix and a coating layer;
[0393] The coating layer completely covers the substrate;
[0394] The component of the coating layer is Li3PO4.
[0395] The mass ratio of the components of the coating layer to the mass ratio of the negative electrode material is 3.0%.
[0396] The above electrolyte is prepared by the following method:
[0397] A solution prepared by mixing lithium salt LiPF6 and non-aqueous organic solvent (ethylene carbonate (EC): diethyl carbonate (DEC): propylene carbonate (PC): propyl propionate (PP): vinylene carbonate (VC)) = 20:30:20:28:2, mass ratio) in a mass ratio of 8:92 is used as the electrolyte of the lithium ion battery.
[0398] The method for preparing the above-mentioned negative electrode material comprises the following steps:
[0399] S1: Red phosphorus and graphite were mixed in a mass ratio of 1:1 and dissolved in 100 mL of deionized water, stirred evenly, and ball-milled at a speed of 500 rpm for 2 h. After filtering and washing, the product was placed in a vacuum drying oven at 80°C and dried overnight to obtain a matrix material.
[0400] S2 adds 3.0% by mass of Li3PO4 (the mass of Li3PO4 accounts for the mass percentage of Li3PO4 and the mass percentage of the matrix material) to the matrix material, and then adds 100mL of anhydrous ethanol as a dispersant, stirs evenly to obtain a mixture, pours the above mixture into a hydrothermal reactor, and places the hydrothermal reactor into an electric constant temperature blast drying oven, and performs hydrothermal reaction at 200°C for 20 hours to obtain the above negative electrode material.
[0401] The preparation of the above battery comprises the following steps:
[0402] After preparing the positive electrode and the electrolyte, the components of the lithium ion battery are assembled to obtain the above lithium ion battery.
[0403] Comparative Example 1
[0404] The difference between Comparative Example 1 and Example 1 is that the negative electrode material of Comparative Example 1 has only a substrate but no coating layer.
[0405] Comparative Example 2
[0406] The difference between Comparative Example 2 and Example 15 is that in step S2 of Comparative Example 2, the component of the coating layer is 3.0 mass % Li2C2O4.
[0407] Specific:
[0408] A negative electrode material is a core-shell structure, comprising a matrix and a coating layer;
[0409] The coating layer completely covers the substrate;
[0410] The component of the coating layer is Li2C2O4.
[0411] The mass ratio of the components of the coating layer to the mass ratio of the negative electrode material is 3.0%.
[0412] The method for preparing the above-mentioned negative electrode material comprises the following steps:
[0413] S1: Red phosphorus and graphite were mixed in a mass ratio of 1:1 and dissolved in 100 mL of deionized water, stirred evenly, and ball-milled at a speed of 500 rpm for 2 h. After filtering and washing, the product was placed in a vacuum drying oven at 80°C and dried overnight to obtain a matrix material.
[0414] S2: Add 1.5% by mass of LiF and 1.5% by mass of Li3PO4 (the mass of LiF and Li3PO4 accounts for the mass of LiF and Li3PO4 and the mass of the matrix material) to the matrix material, then add 100 mL of anhydrous ethanol as a dispersant, stir evenly to obtain a mixture, pour the above mixture into a hydrothermal reactor, put the hydrothermal reactor into an electric constant temperature blast drying oven, and perform hydrothermal reaction at 200°C for 20 hours to obtain the above negative electrode material.
[0415] A lithium ion battery comprises a positive electrode, a negative electrode and an electrolyte, wherein the negative electrode comprises the negative electrode material and the electrolyte comprises an organic nitrile additive.
[0416] Performance Testing:
[0417] The lithium ion batteries of Examples 1-21 and Comparative Examples 1-2 were subjected to the following tests. The test results are shown in Table 1.
[0418] (1) Cycle retention rate test
[0419] Take 5 lithium ion batteries prepared in the comparative example and the example, respectively, and repeatedly charge and discharge the lithium ion batteries through the following steps, and calculate the cycle capacity retention rate of the lithium ion batteries.
[0420] First, in an environment of 25°C, the first charge and discharge were carried out, and constant current and constant voltage charging was performed at a charging current of 0.1C (i.e., the current value at which the theoretical capacity is completely discharged within 10 hours) until the upper limit voltage was 4.5V, and then constant current discharge was performed at a discharge current of 1C until the final voltage was 3V, and the discharge capacity of the first cycle was recorded; then 100 charge and discharge cycles were carried out, and the discharge capacity of the 100th cycle was recorded.
[0421] Cycle capacity retention rate=(discharge capacity at the 100th cycle / discharge capacity at the first cycle)×100%.
[0422] (2) Cyclic expansion rate test
[0423] Five lithium-ion batteries prepared in the comparative example and the example were taken respectively, and the lithium-ion secondary batteries were repeatedly charged and discharged through the following steps, and the cycle expansion rate of the lithium-ion batteries was calculated.
[0424] First, the initial thickness of the battery was measured at room temperature. Then, in an environment of 25°C, constant current charge and discharge were performed 100 times at a discharge current of 1C (i.e., the current value at which the theoretical capacity is completely discharged within 1 hour). The battery was then fully charged to 4.5V and the battery thickness after the 100th cycle was measured.
[0425] Cycle expansion ratio = (battery thickness after 100th cycle - initial thickness before cycle) / initial thickness before cycle × 100%.
[0426] (3) High temperature storage test
[0427] Five lithium-ion batteries prepared in the comparative example and the example were taken respectively, and the lithium-ion secondary batteries were repeatedly charged and stored at high temperatures through the following steps, and the high-temperature storage expansion rate of the lithium-ion batteries was calculated.
[0428] First, at 25°C, after charging to 4.5V (cut-off current is 0.02C) with 0.5C constant current and constant voltage, the initial thickness of the battery was measured, and then the battery cell was transferred to a high-temperature oven at 85°C, and the battery cell thickness was tested after being stored at 85°C for 6 hours.
[0429] High temperature storage expansion rate = (battery thickness after high temperature storage - initial thickness before high temperature storage) / initial thickness before high temperature storage × 100%.
[0430] Table 1
[0431]
[0432] As can be seen from Table 1, although the batteries of Examples 1-16 all have a higher cycle retention rate and a lower cycle expansion rate, it can be seen from Example 1-9 that the less the coating amount, the smaller the high-temperature storage expansion rate, but it will deteriorate the cycle retention rate. Therefore, in order to balance the performance of the two, a coating amount of 3% is used as the optimal coating condition. The difference between Examples 7, 10 and 11 is the different hydrothermal temperatures, among which the 200°C hydrothermal temperature has the best effect; the difference between Examples 13-16 is the different coating materials, when the coating materials are LiF and Li3PO4, the effect is best. By using different contents of nitrile additives in Examples 7, 19 and 20, it can be seen that 0.5% organic nitrile additives have the smallest high-temperature storage expansion. It can be seen from Example 21 that although a coating layer is introduced into the negative electrode of this embodiment, the problem of negative electrode expansion is alleviated and the cycle performance of the battery is improved, it also leads to an increase in the high-temperature storage expansion rate. It can be seen from Examples 7, 17, and 18 that through experimental comparison of a series of additives, it is found that AND has the best effect. Therefore, the effect is better when the additive content W1 and the coating amount W2 are controlled within the range of 0.09<W1 / (W1+W2)<0.91. Among them, the phosphorus-carbon negative electrode material of the composite coating material of LiF and Li3PO4 with a coating amount of 3% under 200℃ hydrothermal conditions has the best effect on the cycle capacity retention rate and cycle expansion rate of the lithium-ion battery. It shows that the negative electrode material provided by the present invention has better structural stability and electrochemical performance. The coating layer material in the negative electrode material of the present invention can effectively reduce the expansion of the phosphorus-carbon negative electrode during the deintercalation and extraction of lithium from the phosphorus-carbon negative electrode material, reduce the problem of phosphorus-carbon particle breakage caused by continuous circulation, and improve the interface stability of the negative electrode material, which may cause the problem of decomposition and gas production. At this time, the additive in the electrolyte can effectively suppress this high-temperature gas production problem. At the same time, the coating layer can also reduce the corrosion of the electrolyte on the phosphorus-carbon negative electrode material. The synergistic effect of the two can ensure that the electrochemical performance of the phosphorus-carbon negative electrode material is improved without deteriorating the cycle gas production performance.
[0433] The above are only embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent transformations made using the contents of the present invention specification, or directly or indirectly applied in related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A lithium ion battery, characterized in that: The lithium-ion battery comprises a negative electrode and an electrolyte; The negative electrode comprises a negative electrode material, and the negative electrode material is a core-shell structure, comprising a matrix and a coating layer; The coating layer completely or partially covers the substrate; The coating layer comprises LiF, Li3N, Li3PO4, Li2B4O7, Li4Ti5O 12 At least one of .
2. A lithium ion battery according to claim 1, characterized in that: The mass ratio of the components of the coating layer to the mass ratio of the negative electrode material is 0.05%-5%.
3. A lithium ion battery according to claim 1, characterized in that: The coating layer comprises Li2B4O7 and Li4Ti5O in a mass ratio of 1-1.5:1-1.5 12 .
4. A lithium ion battery according to claim 1, characterized in that: The coating layer comprises LiF and Li3PO4 in a mass ratio of 1-1.5:1-1.
5.
5. A lithium ion battery according to claim 1, characterized in that: The components of the electrolyte include organic nitrile additives.
6. A lithium ion battery according to claim 5, characterized in that: The organic nitrile additive includes at least one of 1,2-adiponitrile, 1,3,6-hexanetrinitrile and 1,3-succinonitrile.
7. A lithium ion battery according to claim 5, characterized in that: The amount of the organic nitrile additive added is W1, and the amount of the component added in the coating layer is W2. There is the following relationship between W1 and W2: 0.09<W1 / (W1+W2)<0.
91.
8. A lithium ion battery according to claim 6, characterized in that: The ratio of W1 to W2 is 0.3-1:0.05-5.
9. A method for preparing a lithium ion battery according to any one of claims 1 to 8, characterized in that: The following steps are involved: After preparing the negative electrode and the electrolyte, the components of the lithium ion battery are assembled to obtain the lithium ion battery.
10. The method according to claim 9, characterized in that: The method for preparing the negative electrode comprises the following steps: S1 takes the base material and ball-mills it to obtain a base; S2 mixes the matrix and coating material and obtains the negative electrode material through a hydrothermal reaction.
Citation Information
Cited By
Negative electrode material, preparation method thereof and lithium ion battery
CN119994038A